The Relationship Between Socio-Economical and Pregnancy Spacing with the Incidence of Chronic Energy Deficiency (CED) in Pregnant Women at the Balen Community Health Center - Yuli Anggraeni; Siti Patonah; Wiwik Utami; Fidrotin Azizah (PT. Radja Intercontinental Publishing, 2026)
Chronic Energy Deficiency (CED) remains a serious nutritional problem among pregnant women in Indonesia, particularly in the Balen Community Health Center (Puskesmas) area of ​​Bojonegoro Regency. Socioeconomic status and pregnancy spacing are suspected to contribute to the incidence of CED. The purpose of this study was to determine the relationship between socioeconomic status and pregnancy spacing and the incidence of CED in pregnant women. This study used a cross-sectional design with a sample size of 44 pregnant women drawn using simple random sampling. The independent variables were socioeconomic status and pregnancy spacing, while the dependent variable was the incidence of CED as measured by mid-upper arm circumference (MUAC). Data analysis used the Spearman's Rho test with a significance level of <0.05. The study showed that less than half of the pregnant women had low socioeconomic status (19 women (43.2%), and most of the pregnant women had a safe/ideal pregnancy spacing (37 women (84.1%). The results of the analysis using sperm rank showed a significant association between economic status and the incidence of CED (p = 0.000). women, while pregnancy spacing did not show a significant association. Nutrition education interventions and ideal pregnancy planning are needed to prevent CED.